Cassava value chain development through partnership and stakeholders platform in Cameroon - Njukwe, E.; Hanna, R.; Sarr, S.; Shigeru, A.; Kirscht, H.; Mbairanodji, A.; Ngue-Bissa, T.; Tenkouano, A. (Journal Issues Limited, 2014)
In order to understand product flows of cassava and actors along its value chain, a study was conducted in three out of the five antennas of National Program for Roots and Tuber Development (PNDRT); South and Centre, West and North West and East regions in Cameroon with the aid of structured questionnaires, interviewing producers, processors, transporters, marketers and consumers. It was observed that the major challenge affecting cassava enterprise development were age (60.84%) above 45 and education status (76.67%) below primary including poor organization and planning while women represent 65.83%. Transportation is dominated by head or back-load (60%) while 32.5% of cassava is consumed fresh and 51.67% of the product is sold in village market. In a partnership agreement between the International Institute of Tropical Agriculture (IITA) and PNDRT to enhance cassava production, IITA adopted the value chain approach in research-for-development that guarantees the coverage of production to consumption and considers all groups from farmers to consumers and developed a variety of cassava processing techniques to broaden the range of products derived from cassava. To achieve successful partnership, collaboration is formalized through appropriate agreements that clearly define responsibilities and expectations and required for a specific level of product based on partner’s category, status, geographic location, years of experience, current activities and capacity.